Comparison of the Efficacy of Two Different Local Anesthesia Techniques for Mesotherapy in Temporal Region Alopecia - Nagaja, Sharanika A; John, Rubin S; Kumar, Santhosh P; Krishnan, Murugesan (Curēus (Palo Alto, CA), 2024)
Introduction Mesotherapy is a wide range of minimally invasive injections. In mesotherapy, a mixture of various tonics is injected into the skin. These include plant extracts, various medications, vitamins, enzymes, hormones, growth factors, and other factors that will help treat alopecia. Most commonly, a mixture of platelet-rich plasma (PRP) and vitamins is used. In mesotherapy treatment for hair regrowth in the temporal region, zygomaticotemporal nerve blocks, supratrochlear nerve blocks, and supraorbital nerve blocks are given. The zygomaticotemporal nerve, supraorbital nerve, and supratrochlear nerve are the branches of the trigeminal nerve. They provide sensation on the lateral side of the forehead, which is the temple region.  Methods A sample size of 100 people was taken for the study who were undergoing mesotherapy in the bilateral temporal region for alopecia. Each group had 50 subjects: group I was given supratrochlear, supraorbital, and zygomaticotemporal nerve blocks as local anesthesia techniques, and group II was given supratrochlear and supraorbital nerve blocks. PRP was injected using an insulin syringe. Pain was assessed using a visual analog scale (VAS). Results During the procedure, a mean VAS of 1 and 3 was observed in groups I and II, respectively, during the procedure (p-value 0.023). A mean VAS of 3 and 5 was observed in groups I and II, respectively, after three hours (p-value 0.000). This shows a significant difference in the pain experienced by the subjects between the groups.  Conclusion This study proves that the zygomaticotemporal nerve, used along with supratrochlear and supraorbital nerve blocks, is better at producing analgesia and reducing pain.